Distributions of Countable Models of Quite O-Minimal Ehrenfeucht Theories - Kulpeshov, Beibut; Sudoplatov, Sergey (Eurasian Mathematical Journal, 2020)
We describe Rudin–Keisler preorders and distribution functions of numbers of limit models for quite o-minimal Ehrenfeucht theories. Decomposition formulas for these distributions are found.